Physiochemical Properties of Polysaccharides Extracted From green algae Cladophora crispata - Al-Aumara, Suham W. A.; Al-Mossawi, Aum–El-Basher H. J.; Al-Ali, Rawdah M .A. (Iraqi Journal of Aquaculture, 2021)
Extraction of polysaccharides from green algae Cladophora crispata was studied. Algae was collected from Karmat Ali River in Basrah. Polysaccharides was extracted by sodium carbonate Na2CO3 and the properties for it were studied. The result showed that the relative viscosity was increased with the increase of concentration and decrease with the increasing of temperature the highest viscosity was 11.0020 in 30°C and the lowest was 8.0576 in 50 °C. The ability of polysaccharides for water absorbtion and fat binding was noticed that it was increased with the increasing of the concentration, the percentage of polysaccharides solubility was 69.72%, and it was higher than sodium alginate (65.68%). the results also showed decreased of foaming of polysaccharides because of it s high viscosity.